5(x-3)-2(x+4)=(x-3)+4(x-1)

Simple and best practice solution for 5(x-3)-2(x+4)=(x-3)+4(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)-2(x+4)=(x-3)+4(x-1) equation:


Simplifying
5(x + -3) + -2(x + 4) = (x + -3) + 4(x + -1)

Reorder the terms:
5(-3 + x) + -2(x + 4) = (x + -3) + 4(x + -1)
(-3 * 5 + x * 5) + -2(x + 4) = (x + -3) + 4(x + -1)
(-15 + 5x) + -2(x + 4) = (x + -3) + 4(x + -1)

Reorder the terms:
-15 + 5x + -2(4 + x) = (x + -3) + 4(x + -1)
-15 + 5x + (4 * -2 + x * -2) = (x + -3) + 4(x + -1)
-15 + 5x + (-8 + -2x) = (x + -3) + 4(x + -1)

Reorder the terms:
-15 + -8 + 5x + -2x = (x + -3) + 4(x + -1)

Combine like terms: -15 + -8 = -23
-23 + 5x + -2x = (x + -3) + 4(x + -1)

Combine like terms: 5x + -2x = 3x
-23 + 3x = (x + -3) + 4(x + -1)

Reorder the terms:
-23 + 3x = (-3 + x) + 4(x + -1)

Remove parenthesis around (-3 + x)
-23 + 3x = -3 + x + 4(x + -1)

Reorder the terms:
-23 + 3x = -3 + x + 4(-1 + x)
-23 + 3x = -3 + x + (-1 * 4 + x * 4)
-23 + 3x = -3 + x + (-4 + 4x)

Reorder the terms:
-23 + 3x = -3 + -4 + x + 4x

Combine like terms: -3 + -4 = -7
-23 + 3x = -7 + x + 4x

Combine like terms: x + 4x = 5x
-23 + 3x = -7 + 5x

Solving
-23 + 3x = -7 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-23 + 3x + -5x = -7 + 5x + -5x

Combine like terms: 3x + -5x = -2x
-23 + -2x = -7 + 5x + -5x

Combine like terms: 5x + -5x = 0
-23 + -2x = -7 + 0
-23 + -2x = -7

Add '23' to each side of the equation.
-23 + 23 + -2x = -7 + 23

Combine like terms: -23 + 23 = 0
0 + -2x = -7 + 23
-2x = -7 + 23

Combine like terms: -7 + 23 = 16
-2x = 16

Divide each side by '-2'.
x = -8

Simplifying
x = -8

See similar equations:

| a^4-a^2+5=0 | | 3(x+8)=38-4x | | cos3y=1/2 | | 3x^2+41x-170=0 | | X-(2x+5)=-2(x+4)+19 | | -(2x+5)=2(x+4)+19 | | 60x/120x | | 4(x+4)=2(x+20) | | -8(3y+5)+y=-1 | | 25x+20=5x+40 | | 6x+18=-10 | | 2(-2y+5)-y=-5 | | 3(1.8+-0.4y)-y=8 | | 3y+25=2y+50 | | logy=alogx+b | | 9+-4y=9-4y | | -6x-5y=1 | | 4+3y-3y=4 | | 9n+68=7n+2n-2 | | 0=-4-4x-3x^2 | | 19+(-4y)+4y=19 | | 9x+1=3x-7 | | 9x+1=3x-1 | | 3(4+-2y)+4y=10 | | Y=-4/7x-1/7 | | 15x^2+40x-5=0 | | log(x)=0.40338 | | n^2-12n+21=0 | | e^8-9x=1168 | | 1/3(9)cubed | | 3/x-12/x-3=1 | | X^2+x+121=0 |

Equations solver categories